41.6k views
25 votes
Solve for z. assume the equation has a solution for z.
−p⋅(d+z)=−2z+59
Plz Help

Solve for z. assume the equation has a solution for z. −p⋅(d+z)=−2z+59 Plz Help-example-1
User Charleston
by
4.6k points

2 Answers

5 votes

Answer:

z= −p−d/84+51p

Explanation:

KA

User Przemek Piechota
by
4.5k points
4 votes

Answer:


z= (pd-59)/(-2+p)

Explanation:

-p(d+z)=-2z+59

-pd-pz=-2z+59

lets bring all z integers on one side

-2z+pz = -pd-59

z(-2+p)=-pd-59

z = (pd-59) / (-2+p)

User Greatvovan
by
4.6k points